Relationship between Leverage, Company Size and Total Assets - Sugeng Suroso (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to examine how leverage and firm size influence total assets in the banking industry on the Indonesian stock exchange for the 2019-2021 period. The shares in banking companies are either partially or simultaneously. The data used comes from the financial statements of each company and comes from IDX. . The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2009-2013. The number of samples that meet these criteria are 9 companies from 32 banks. To prove the hypothesis was tested using multiple linear regression analysis, t test, and f test and to prove there was no deviation in the regression results were tested using the classical assumption test (normality, multicollinearity, heteroscedasticity and autocorrelation). Multiple regression equation (Y) = LN TA = 2.620 + 0.001 DER + 0.996 LN UP + 0.007 OWN. The constant coefficient a = 2.620, meaning that if all independent variables have zero (0) then the total asset growth is 2.620. The coefficient 1 = 0.001, is the DER regression coefficient value of 0.001, meaning that every one unit increase in DER, the growth of total assets will increase by 0.001 with the assumption that the other independent variables of the regression model are fixed. The DER regression coefficient is positive, meaning that between DER and total asset growth is directly proportional, meaning that if DER increases, total asset growth will decrease by the regression coefficient. The coefficient 2 = 0.966, is the value of the firm size regression coefficient of 0.996, meaning that for every one unit increase in firm size, the growth of total assets will increase by 0.996 assuming the other independent variables of the regression model are fixed. The regression coefficient of firm size is positive, which means that the size of the company and the growth of total assets is directly proportional, meaning that if the size of the company increases, the growth of total assets will decrease by the regression coefficient. The coefficient 3 = 0.007, is the regression coefficient value of ownership (dummy variable) of 0.007, meaning that ownership affects the LN of total assets. If DER and LN the size of state-owned and non-BUMN banking companies increases by one unit. When the DER and LN sizes of state-owned and non-BUMN banking companies increase by one unit, the difference in the average value of LN total assets is 1.004.